Prevalence of arsenic contamination in rice and the potential health risks to the Bahamian population—A preliminary study - Watson, Carlton; Gustave, Williamson (Frontiers in Environmental Science, 2022)
Rice is among the most important staple foods worldwide. However, the consumption of rice products poses a potential health risk since rice is known to accumulate arsenic (As) in their grains. In The Bahamas, although rice is heavily consumed, it is not grown locally. Instead, all the consumed rice are imported. Recent food surveys in the major rice exporting countries have shown that a significant portion of their market rice products are contaminated with As. However, to date, the prevalence of As in the rice foods available in The Bahamas remains unknown. Therefore, in this study we surveyed the occurrence of As in rice products on sale in the Bahamian market. A total of 21 different rice brands were collected. The As concentration and the potential health risk were estimated by target hazard quotient(THQ), hazard index (HI), and Lifetime Cancer Risk(LCR). Our results showed that only 2% of the samples had an estimated inorganic arsenic (iAs) concentration above the World Health Organization(WHO) safety limits (200 µg/kg) - which is based on global average consumption. However, when we factor for average rice consumption in The Bahamas, 79% of the rice samples had iAs concentration values indicative of carcinogenic risks and 57% had iAs concentration values that suggested non-carcinogen health risks. Based on our results, we recommend urgent follow up studies to further test rice varieties that show the greatest LCR and HI values and to also broaden the study to include more off-brand/generic varieties, cooked rice as well as drinking water.